2021
DOI: 10.3389/fnut.2020.593599
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Inverse Associations Between Beans Intake, Serum Urate Levels, and Hyperuricemia: A Cross-Sectional Analysis Based on the Henan Rural Cohort Study

Abstract: Background and Aims: Beans are rich in purines, which are important substances that lead to elevated serum urate, especially exogenous purines. Few studies were conducted to assess the relationship between beans intake and serum urate or hyperuricemia, especially in rural people. The purpose of this study was to validate the association by gender in the rural Chinese population.Methods: A total of 38,855 participants aged 18–79 years old were enrolled from the Henan Rural Cohort Study (Registration number: Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…High meat consumption, particularly red meat and seafood, have long been documented as a risk factor for HUA [ 10 ]. In contrast, higher soy food intake was found to be linked to lower serum uric acid levels in adults by a recent cross-sectional research conducted in Henan Province, China [ 36 ]. Previous studies have shown that although legumes are considered a purine-rich food, some special constituents such as phytic acid and polyphenols may have a beneficial influence on uric acid levels [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…High meat consumption, particularly red meat and seafood, have long been documented as a risk factor for HUA [ 10 ]. In contrast, higher soy food intake was found to be linked to lower serum uric acid levels in adults by a recent cross-sectional research conducted in Henan Province, China [ 36 ]. Previous studies have shown that although legumes are considered a purine-rich food, some special constituents such as phytic acid and polyphenols may have a beneficial influence on uric acid levels [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Soy foods are an excellent source of essential nutrients, including proteins, soluble dietary fibers, unsaturated fatty acids, iron, and isoflavones, constituting bioactive components ( 29 ). Many studies have found beneficial effects of soy or beans consumption on multiple chronic metabolic health outcomes, including hypertension, diabetes, hyperuricemia and dyslipidemia ( 9 , 21 , 30 , 31 ), which are relevant risk factors of CKD. Nevertheless, few studies have investigated the direct relationship between soy food/beans intake and CKD risk, and no large population-based epidemiologic studies have been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, beans intake in this study was identified as the total consumption of all beans and products commonly eaten by local people, such as soybean, lentil, red bean, mung bean, black bean, pea, tofu, soy milk, dried tofu, vegetarian chicken, etc. ( 21 ). Furthermore, all participants were divided into four groups according to quartiles of daily total beans intake in the main analyses: Q1, beans intake <6.67 g/d; Q2, beans intake =6.68–16.67 g/d; Q3, beans intake =16.68–50 g/d; and Q4, beans intake >50 g/d.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations